Neonatal severe intractable diarrhoea as the presenting manifestation of an unclassified congenital disorder of glycosylation (CDG-x). Issue 3 (1st November 2001) - Mention, K; Michaud, L; Dobbelaere, D; Guimber, D; Gottrand, F; Turck, D
Abstract : A case of severe and protracted diarrhoea is reported, which started in the neonatal period and progressively associated with neurological impairment, dysmorphy, hepatosplenomegaly, and hepatic insufficiency, from which the patient died at 2 years of age. Isoelectric focusing of serum transferrin showed a congenital disorder of glycosylation type I pattern but the basic defect could not be identified. This observation shows that congenital disorder of glycosylation is a cause of intractable diarrhoea in neonates.